Linguistics at University Level: The Challenge of its Learning Process in a Program of Bilingual Education - Rojas Molina, Sandra Liliana (GIST – Education and Learning Research Journal, 2014)
The purpose of this document is to share the first phase of an ongoing research project that was born due to the concern of finding alternative ways to present and develop topics related to linguistics and applied linguistics to students in a bilingual education teaching program in Bogotá, Colombia. This first phase has consisted in gathering theoretical information related to the reasons to include linguistics and applied linguistics as subjects in an undergraduate program that trains future language teachers, the differentiation between these two areas of knowledge, and the contents that are involved within them. This article also proposes to take already existing theories about language and content teaching and relate them to the teaching of linguistics and applied linguistics through the design of units using the tools offered by the TWIOP (Two-Way Immersion Observation Protocol) and class work based on problems, tasks and projects.